Gut Microbiota-Based Pharmacokinetics and the Antidepressant Mechanism of Paeoniflorin - Yu, Jin-Bo; Zhao, Zhen-Xiong; Peng, Ran; Pan, Li-Bin; Fu, Jie; Ma, Shu-Rong; Han, Pei; Cong, Lin; Zhang, Zheng-Wei; Sun, Li-Xin; Jiang, Jian-Dong; Wang, Yan (Frontiers in Pharmacology, 2019)
Paeoniflorin, the main component of Xiaoyao Wan, presents low oral bioavailability and unclear antidepressant mechanism. To elucidate the potential reasons for the low bioavailability of paeoniflorin and explore its antidepressant mechanism from the perspective of the gut microbiota, here, a chronic unpredictable depression model and forced swimming test were firstly performed to examine the antidepressant effects of paeoniflorin. Then the pharmacokinetic study of paeoniflorin in rats was performed based on the gut microbiota; meanwhile, the gut microbiota incubated with paeoniflorin in vitro was used to identify the possible metabolites of paeoniflorin. Molecular virtual docking experiments together with the specific inhibitor tests were applied to investigate the mechanism of paeoniflorin metabolism by the gut microbiota. Finally, the intestinal microbiota composition was analyzed by 16S rRNA gene sequencing technology. The pharmacodynamics tests showed that paeoniflorin had significant antidepressant activity, but its oral bioavailability was 2.32%. Interestingly, we found paeoniflorin was converted into benzoic acid by the gut microbiota, and was mainly excreted through the urine with the gut metabolite benzoic acid as the prominent excreted form. Moreover, paeoniflorin could also regulate the composition of the gut microbiota by increasing the abundance of probiotics. Therefore, the metabolism effect of gut microbiota may be one of the main reasons for the low oral bioavailability of paeoniflorin. Additionally, paeoniflorin can be metabolized into benzoic acid via gut microbiota enzymes, which might exert antidepressant effects through the blood-brain barrier into the brain.